Peningkatan Pemahaman Menulis Puisi melalui Aplikasi Benime pada Siswa Kelas X SMK Musda Perbaungan - Rahmadani, Selvi Kurnia; Lubis, Hasrita; Kartika, Rika (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to improve the understanding of writing poetry in Class X at SMK Musda Perbaungan. The research involved a population of 381 students across various classes, with a sample size of 36 students from class X TKJ 1. Data were collected through interviews, observations, and questionnaires. The study utilized the Research and Development (R&D) method by Borg and Gall, which includes ten stages: need analysis, media planning, initial product development, product trial, initial product revision, product improvement, main field trial, product revision (large group), final product revision, and product dissemination. Results indicated that teaching materials for writing poetry, supported by the Benime application, significantly enhanced students' understanding. Material experts rated the materials as "Very Feasible" (94%) and "Feasible" (84%), while media experts gave ratings of "Very Feasible" (90%) and "Feasible" (80%). The effectiveness stage of the development process yielded an "Effective" rating (80%), demonstrating the application's positive impact on poetry writing skills.